Histopathological study of the testes in three genetic lines of Japanese quail (Coturnix japonica) exposed to different doses of L-Arginine - Ahmed Shaker; israa Abd Alsada; Questan Ameen; Luay Alsalihi; Adel Hussen (Basrah Journal of Veterinary Research, 2025)
The purpose of the study was to investigated the histological effect dietary L-arginine supplementation at 0%, 5%, and 10% above National Research Council recommendations on the testes of 225 male Japanese quail from three genetic lines (white, Brown, and gray). The current study was conducted from December 6, 2022, to July 1, 2023, at the poultry farm of Kirkuk University's animal production department, College of Agriculture. Initially, the Directorate of Agricultural Research-Baghdad. Birds were divided by color into three groups and fed diets containing different arginine levels from age 30 to 90 days. Testes from selected birds were examined histologically after H&E staining. Results showed that 5% arginine (S2) induced significant spermatogenic activity in all groups, with the most notable effect in gray quail (thickened basement membranes, increased spermatogenesis, and fat infiltration). The Brown line showed moderate changes, while the white line exhibited only mild stimulation with no fat infiltration. At 10% arginine (S3), the gray line displayed severe histopathological changes, including basement membrane thickening, Sertoli cell disruption, fat infiltration, and signs of early lipoma formation. The Brown line exhibited signs of hyperplasia, while the white line showed enhanced spermatogenesis and sperm maturation with minimal adverse effects. In conclusion, gray quail were highly sensitive to arginine supplementation, Brown quail showed a moderate response, and white quail demonstrated increased spermatogenic activity with minimal histological damage.